2011
DOI: 10.1038/ncomms1605
|View full text |Cite
|
Sign up to set email alerts
|

PKA regulatory subunits mediate synergy among conserved G-protein-coupled receptor cascades

Abstract: G-protein-coupled receptors sense extracellular chemical or physical stimuli and transmit these signals to distinct trimeric G-proteins. Activated Gα-proteins route signals to interconnected effector cascades, thus regulating thresholds, amplitudes and durations of signalling. Gαs- or Gαi-coupled receptor cascades are mechanistically conserved and mediate many sensory processes, including synaptic transmission, cell proliferation and chemotaxis. Here we show that a central, conserved component of Gαs-coupled r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
49
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 59 publications
3
49
0
Order By: Relevance
“…It has been reported that Rac1 participates to promote the Raf-MekErk cascade (16,(34)(35)(36). To investigate the role of GTP-Rac1 in Erk1/2 activation, we used HEK293 cells, which show no increase of Erk1/2 phosphorylation in response to Forskolin alone (18). We confirmed observations that exclusively the overexpression of the constitutive active GTP-Rac1 variant activates Erk1/2 (16) (Fig.…”
Section: Pka Rii Subunits Form Protein Complexes With Rac1 In Vitro Asupporting
confidence: 69%
See 4 more Smart Citations
“…It has been reported that Rac1 participates to promote the Raf-MekErk cascade (16,(34)(35)(36). To investigate the role of GTP-Rac1 in Erk1/2 activation, we used HEK293 cells, which show no increase of Erk1/2 phosphorylation in response to Forskolin alone (18). We confirmed observations that exclusively the overexpression of the constitutive active GTP-Rac1 variant activates Erk1/2 (16) (Fig.…”
Section: Pka Rii Subunits Form Protein Complexes With Rac1 In Vitro Asupporting
confidence: 69%
“…These processes are distinct from the mechanism we describe here, where Rac-anchored PKA activities directly contribute to the activation of downstream effectors of GTP-Rac signaling leading to Erk1/2 activation. Another GTPase, which we have identified in the same screen to be a binary interaction partner of PKA RII subunits, is a component of the trimeric G protein complex Gαi, although without AKAP features (18). In contrast to Rac1:PKA, complex formation of RII subunits with Gαi was observed in response to cAMP elevation.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations